Effect of thermal challenge on plasma gonadotropin levels and ovarian steroidogenesis in female maiden and repeat spawning Tasmanian Atlantic salmon (Salmo salar) - Kelli Anderson; Swanson, P; Pankhurst, N; King, H; Elizur, A (2012)
Exposure of female Atlantic salmon to elevated temperature can result in a dramatic reduction in egg fertility and embryo survival. Reductions in plasma 17β-estradiol (E 2 ) levels are associated with much of the observed reduction in reproductive performance; however, the molecular basis for reduced E 2 levels remains unknown. This study examined gene expression of ovarian steroidogenic enzymes and plasma levels of gonadotropins in maiden and repeat spawning Atlantic salmon exposed to higher than normal temperatures. Circulating levels of follicle stimulating hormone (Fsh) were significantly elevated in both maiden and repeat spawning fish maintained at 22 °C compared to 14 °C during vitellogenesis, but plasma luteinising hormone levels were mostly unaffected. In contrast, gene expression of the ovarian p450 aromatase a and cholesterol side chain cleavage protein were depressed at 22 °C compared to 14 °C. Hepatic gene expression of estrogen receptor alpha did not change with thermal challenge. The results show that the ovarian response to Fsh is inhibited at 22 °C, at least partly as a result of reduced expression of genes coding for steroidogenic enzymes.